Exploring Kurikulum Merdeka: ELT Practices in an Islamic Secondary School in Batam - Nurlaily; Maya Marsevani; Tasya Meylarisman; Iffani Junita Tambunan; Zico Kevin Mamusung; Vriskila Piolawanti (STAIN Majene, 2025)
Curriculum reforms play a vital role in improving the quality of teaching and learning, particularly in language. Kurikulum Merdeka introduces a student-centered approach to learning in Indonesia. Yet little is known about how it is implemented in Islamic secondary schools where national and religious goals must be aligned. This study investigates English teachers’ perspectives on the curriculum’s effectiveness, challenges, and best practices in this context. A qualitative case study was conducted through classroom observations, interviews, and field notes. Findings indicate that the curriculum enhances student engagement, particularly when instruction involves real-life themes, technology, and task choice. Teacher 1 noted that even students who “usually sleep in class now want to learn,” while Teacher 2 found learners more active when discussing “issues happening around us.” However, limited training, infrastructure constraints, and unclear assessment practices created implementation challenges. Teachers addressed these issues through differentiated instruction, authentic materials, peer collaboration, and ongoing professional learning. This study contributes context-specific insights into how English instruction adapts to Kurikulum Merdeka in Islamic schooling. It recommends more practical teacher training, improved digital access, and clearer assessment guidelines. Future research should examine diverse regions and track long-term development of learner autonomy under the curriculum.